Epigenetic Regulation of BST-2 Expression Levels and the Effect on HIV-1 Pathogenesis - Singh, Ravesh; Ramsuran, Veron; Naranbhai, Vivek; Yende-Zuma, Nonhlanhla; Garrett, Nigel; Mlisana, Koleka; Dong, Krista L.; Walker, Bruce D.; Abdool Karim, Salim S.; Carrington, Mary; Ndung’u, Thumbi (Frontiers in Immunology, 2021)
HIV-1 must overcome host antiviral restriction factors for efficient replication. We hypothesized that elevated levels of bone marrow stromal cell antigen 2 (BST-2), a potent host restriction factor that interferes with HIV-1 particle release in some human cells and is antagonized by the viral protein Vpu, may associate with viral control. Expression levels of BST-2 mRNA were measured using a real-time PCR assay and protein levels were validated by Western blotting. The expression level of BST-2 showed an association with viral control within two independent cohorts of Black HIV-infected individuals (r=-0.53, p=0.015, and r=-0.62, p=0.0006). DNA methylation was identified as a mechanism regulating BST-2 levels, where increased BST-2 methylation results in lower expression levels and associates with worse HIV disease outcomes. We further demonstrate the ability to regulate BST-2 levels using a DNA hypomethylation drug. Our results suggest BST-2 as a factor for potential therapeutic intervention against HIV and other diseases known to involve BST-2.